Management of Kapuas River Water as a Sustainable Raw Water Source for Drinking Water Supply in Pontianak City - Syahirah Citra Andini; Dwi Nowo Martono; Haruki Agustina (Eduvest - Journal of Universal Studies, 2026)
The Kapuas River in Pontianak City plays a vital role as a source of raw water for drinking water supply and various other needs. However, the quality of the river water is under increasing pressure due to the activities of surrounding communities. A sustainable management strategy is therefore necessary to maintain both water quality and availability, for human consumption as well as ecosystem sustainability. This study employed a mixed-methods approach encompassing descriptive analysis, regression analysis, and a SWOT framework. The findings indicate that the water quality of the Kapuas River is generally still within the applicable quality standards. Communities residing along the river generally collect and treat water prior to use, representing a form of adaptive response to prevailing water quality conditions. The analysis further reveals that fluctuations in basic drinking water tariffs are influenced by the rate of water loss, or Non-Revenue Water (NRW), which constitutes one of the primary challenges in the provision of clean water services. Based on the SWOT analysis, the recommended sustainable management strategy falls within the WO (Weakness–Opportunity) quadrant, signaling the need for increased funding, enhanced resource capacity, and stronger policy support to reinforce the water management system. Furthermore, regular water quality monitoring and consistent follow-up measures are essential steps to ensure that the Kapuas River remains a safe and reliable source of water for the population of Pontianak City.